Bmpr2 Mutant Rats Develop Pulmonary and Cardiac Characteristics of Pulmonary Arterial Hypertension. Issue 7 (12th February 2019) - Hautefort, Aurélie; Mendes-Ferreira, Pedro; Sabourin, Jessica; Manaud, Grégoire; Bertero, Thomas; Rucker-Martin, Catherine; Riou, Marianne; Adão, Rui; Manoury, Boris; Lambert, Mélanie; Boet, Angèle; Lecerf, Florence; et al.
Abstract : Background: Monoallelic mutations in the gene encoding bone morphogenetic protein receptor 2 ( Bmpr2 ) are the main genetic risk factor for heritable pulmonary arterial hypertension (PAH) with incomplete penetrance. Several Bmpr2 transgenic mice have been reported to develop mild spontaneous PAH. In this study, we examined whether rats with the Bmpr2 mutation were susceptible to developing more severe PAH. Methods: The zinc finger nuclease method was used to establish rat lines with mutations in the Bmpr2 gene. These rats were then characterized at the hemodynamic, histological, electrophysiological, and molecular levels. Results: Rats with a monoallelic deletion of 71 bp in exon 1 (Δ 71 rats) showed decreased BMPRII expression and phosphorylated SMAD1/5/9 levels. Δ 71 Rats develop age-dependent spontaneous PAH with a low penetrance (16%–27%), similar to that in humans. Δ 71 Rats were more susceptible to hypoxia-induced pulmonary hypertension than wild-type rats. Δ 71 Rats exhibited progressive pulmonary vascular remodeling associated with a proproliferative phenotype and showed lower pulmonary microvascular density than wild-type rats. Organ bath studies revealed severe alteration of pulmonary artery contraction and relaxation associated with potassium channel subfamily K member 3 (KCNK3) dysfunction. High levels of perivascular fibrillar collagen and pulmonary interleukin-6 overexpression discriminated rats that developed spontaneous PAH and rats that did not develop spontaneous PAH. Finally, detailed assessments of cardiomyocytes demonstrated alterations in morphology, calcium (Ca 2+ ), and cell contractility specific to the right ventricle; these changes could explain the lower cardiac output of Δ 71 rats. Indeed, adult right ventricular cardiomyocytes from Δ 71 rats exhibited a smaller diameter, decreased sensitivity of sarcomeres to Ca 2+, decreased [Ca 2+ ] transient amplitude, reduced sarcoplasmic reticulum Ca 2+ content, and short action potential duration compared with right ventricular cardiomyocytes from wild-type rats. Conclusions: We characterized the first Bmpr2 mutant rats and showed some of the critical cellular and molecular dysfunctions described in human PAH. We also identified the heart as an unexpected but potential target organ of Bmpr2 mutations. Thus, this new genetic rat model represents a promising tool to study the pathogenesis of PAH. Abstract : Supplemental Digital Content is available in the text.